Fundamental Parameters and Evolutionary Scenario of HD 327083 - Nadezhda L. Vaidman; Anatoly S. Miroshnichenko; Sergey V. Zharikov; Serik A. Khokhlov; Aldiyar T. Agishev; Berik S. Yermekbayev (Galaxies, 2025)
In this study, we present refined orbital and fundamental parameters of the Galactic B[e] supergiant binary system HD 327083 using the Bayesian Markov Chain Monte Carlo (MCMC) method applied to the radial velocities data of HD 327083. We found that the system is well described by a circular orbital model with the mass ratio of the components of <semantics>q=1.15±0.07</semantics>. We modeled the evolutionary history of the system using MESA code. Initially, the system was formed by a binary with the orbital period of <semantics>Porb=108</semantics> day, which contained stars with 13.00 <semantics>±<mspace width="3.33333pt"></mspace>0.05</semantics> <semantics>M⊙</semantics> and <semantics>11.50±0.05</semantics> <semantics>M⊙</semantics> masses. They had a relatively slow rotation <semantics>υrot=0.40±0.13υcrit</semantics> and provided a strong stellar wind. The current system age is <semantics>13.6±0.1</semantics> Myr, and the state of the system corresponds to a close filling of the high massive component’s Roche lobe and a beginning of the mass transfer. The mass-transfer event will occur in a short interval of ≲0.1 Myr only. After that, the mass of the post-primary drops to ≈5 <semantics>M⊙</semantics>, the post-secondary mass grows until ≈20 <semantics>M⊙</semantics>, and the binary will convert to a detached system with a long orbital period of ≈700 days.